2012
DOI: 10.2298/sarh1210641m
|View full text |Cite
|
Sign up to set email alerts
|

Dilated cardiomiopathy associated with celiac disease: Case report and literature review

Abstract: Dilated cardiomyopathy associated with celiac disease is a serious condition which requires multidisciplinary approach involving gastroenterologist and cardiologist. Compliance with gluten-free diet is mandatory if patients are to avoid progression of cardiomyopathy. Screening of patients with idiopathic dilated cardiomyopathy for celiac disease is advisable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 7 publications
1
9
0
Order By: Relevance
“…Although our patient had neither retinopathy nor nephropathy or neuropathy, DCM could be the unique complication of T1D [7]. DCM associated to CD (DCM-CD) without family history of cardiac disease and without known etiology was described especially as case reports [12,13]. It is interesting to know that in previously reported cases of DCM-CD, there was an improvement for cardiac function under GFD for those who had LVEF equal or more than 30%.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Although our patient had neither retinopathy nor nephropathy or neuropathy, DCM could be the unique complication of T1D [7]. DCM associated to CD (DCM-CD) without family history of cardiac disease and without known etiology was described especially as case reports [12,13]. It is interesting to know that in previously reported cases of DCM-CD, there was an improvement for cardiac function under GFD for those who had LVEF equal or more than 30%.…”
Section: Discussionmentioning
confidence: 67%
“…It is interesting to know that in previously reported cases of DCM-CD, there was an improvement for cardiac function under GFD for those who had LVEF equal or more than 30%. In the other hand, a worsening of cardiac function in patients who were not compliant with GFD was described [12,13]. Untreated CD patients might have a more severe clinical evolution of DCM compared to the natural evolution of the disease observed in patients with isolated DCM [14].…”
Section: Discussionmentioning
confidence: 99%
“…We, therefore, recommend that patients with myocarditis and iron deficiency anaemia or other signs of malabsorption should be screened for CD, even in the absence of obvious intestinal symptoms. Besides optimal medical treatment of heart failure and CRT, a gluten-free diet and immunosuppression can also be effective [3,9].…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that patients of CD with good adherence to gluten-free diet demonstrate significant recovery of ventricular volumes and function. [ 13 ] Malabsorption resulting in micronutrient deficiencies, for example, of thiamine, calcium, selenium, and carnitine, which are essential components of myocardial contractility and associated gut edema due to cardiac failure, contributes to it. [ 14 ] Other hypotheses which have been suggested include nutritional deficiencies.…”
Section: Discussionmentioning
confidence: 99%